2013
DOI: 10.1007/s10620-013-2870-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Management in Vulnerable Populations: Gaps in Disease Monitoring and Opportunities for Improved Care

Abstract: Background Hepatitis B (HBV) is prevalent in certain US populations and regular HBV disease monitoring is critical to reducing associated morbidity and mortality. Adherence to established HBV monitoring guidelines among primary care providers is unknown. Aims To evaluate HBV disease monitoring patterns and factors associated with adherence to HBV management guidelines in the primary care setting. Methods Primary providers within the San Francisco safety net healthcare system were surveyed for HBV managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
1
39
2
Order By: Relevance
“…Although CHB management entails several straightforward laboratory and imaging tests, a recent survey of primary care providers caring for a predominately Asian American population found that only 43 % were familiar with guidelines on the management of HBV [27]. These findings highlight the role for targeted education among PCPs managing chronic HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Although CHB management entails several straightforward laboratory and imaging tests, a recent survey of primary care providers caring for a predominately Asian American population found that only 43 % were familiar with guidelines on the management of HBV [27]. These findings highlight the role for targeted education among PCPs managing chronic HBV.…”
Section: Discussionmentioning
confidence: 99%
“…The providers in these neighborhoods were often themselves of the same ethnicity as their population served. This is important since Asian providers have been shown to more likely screen for HBV and HCC in Asian American communities[12, 13, 30]. Similarly, practices with more than 25% Asian immigrant patients have previously been shown to be more likely to screen for HCC[30] in HBV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among providers in San Francisco, 70-76% reported regular screening of HBV and 79-96% reported regular HCC surveillance of HBV infected patients. However, a chart review of Asian patients for whom screening was recommended, found only 63% had any screening for HCC in the previous year, and two-thirds of such patients had never had abdominal imaging for HCC as per guidelines [16, 30]. A chart review of over 800 Chinese-speaking patients found that only 65% of patients had been appropriately screened for HBV [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, there is evidence suggesting that, among primary care providers, there is a lack of awareness and insufficient adherence to the current recommendations for CHB management. A number of US studies demonstrated poor compliance with CHB practice guidelines among treating physicians, in particular regarding regular monitoring of CHB status (using markers such as HBV DNA and alanine aminotransferase [ALT]), performance of liver biopsy to guide treatment decisions, treatment initiation among patients considered eligible for anti-HBV therapy, use of recommended agents, and HCC surveillance 14 -16 ; this was partially the result of a lack of familiarity with practice guidelines 15 and was more common among primary care physicians than among specialists. 17 Another study assessing perceptions of CHB among primary care physicians in the US Asian American community showed that despite awareness of the high prevalence of CHB among Asian Americans, 62% of the primary care physicians were unfamiliar with the current major CHB treatment guidelines.…”
mentioning
confidence: 99%